Peranan Integrasi Bisnis Dalam Meningkatkan Efisiensi Operasional Perusahaan (Studi Kasus PT Dland Bimasakti Property) - Nurfadillah Najwa Faraiddin; Cindy Claudia Hutabarat; Ongku Munthe; Nurbaiti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
Business is an effort carried out by an individual or company with the aim of making a profit. In improving company operations, it is necessary to carry out business integration. Business integration is an effort made by a company to increase the company's advantages. The effort made is by combining two or more companies to improve the performance and quality of a company. This research discusses business integration with the aim of knowing the role of business integration in increasing company operational efficiency. In this research, the object of our company is PT Dland Bimasakti Property. In this company they use a technology-based integrated system, namely ERP (Enterprise Resource Planning). The ERP (Enterprise Resource Planning) applications used in this application are Microsoft Dynamics 365 and Odoo. This application is able to increase the company's operational efficiency.